Dampak Financial Distress, Leverage dan Manajemen Laba Terhadap Opini Audit Going Concern pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Farencia Yovanca Kusnadi; Susanto Salim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The disclosure of a company's going concern information, as expressed in the going concern audit opinion, is crucial for financial statement users in making well-informed decisions. This study aims to analyze the impact of financial distress, leverage, and earnings management on the going concern audit opinion in energy sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. The data used in this study are secondary data obtained from the official website of the Indonesia Stock Exchange. The sampling method employed is purposive sampling, resulting in a sample of 39 companies. The data were analyzed using logistic regression with the assistance of the Statistical Package for the Social Sciences (SPSS) version 25. The results of the study indicate that financial distress has a negative effect on the going concern audit opinion. On the other hand, leverage and earnings management do not have a significant effect on the going concern audit opinion.